2013
DOI: 10.1155/2013/903604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Community-Based Cardiac Rehabilitation on Body Composition and Physical Function in Individuals with Stable Coronary Artery Disease: 1.6-Year Followup

Abstract: Objective. To examine long-term changes in physical function and body composition in coronary artery disease (CAD) patients participating in ongoing community-based cardiac rehabilitation (CR). Design. Thirty-four individuals (69.7 ± 8.2 years; 79% men) participated in this longitudinal observational study. Baseline and follow-up assessments included incremental shuttle walk, short physical performance battery, handgrip strength, chair stands, body composition, last year physical activity, and CR attendance. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…There has been limited investigation of communitybased CR maintenance programs, despite suggestions that such programs could improve exercise capacity and facilitate management of cardiovascular risk factors [8,11]. We previously reported on elderly cardiac patients participating in a community-based CR maintenance program [13]. During the 1.6-year follow-up, participants improved lower-body muscle strength, but experienced a decline in handgrip strength and unfavourable changes in body composition, regardless of attendance rates [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been limited investigation of communitybased CR maintenance programs, despite suggestions that such programs could improve exercise capacity and facilitate management of cardiovascular risk factors [8,11]. We previously reported on elderly cardiac patients participating in a community-based CR maintenance program [13]. During the 1.6-year follow-up, participants improved lower-body muscle strength, but experienced a decline in handgrip strength and unfavourable changes in body composition, regardless of attendance rates [13].…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported on elderly cardiac patients participating in a community-based CR maintenance program [13]. During the 1.6-year follow-up, participants improved lower-body muscle strength, but experienced a decline in handgrip strength and unfavourable changes in body composition, regardless of attendance rates [13].…”
Section: Methodsmentioning
confidence: 99%
“…14 Physical exercise influences physical fitness, whose components include flexibility, muscle strength, cardiorespiratory endurance and body composition. 15 The studies by Mandic et al, 16 and Calegari et al, 17 have shown that the regular practice of physical activity has favorable effects on the body composition and functional capacity of individuals with CVD. However, whether the VR intervention as a physical exercise modality has benefits similar to those of the cardiovascular rehabilitation process remains controversial.…”
Section: -629mentioning
confidence: 99%
“…Some of these models are seen in both high-and middle-income countries, such as home- 127,139 and community-based programs. 100,139,140 These programs are found to be as effective as hospital-based CR in reduction of CVD risk factors and mortality in recent systematic reviews. 41,142 Moreover, home-based programs are shown to be as beneficial as supervised programs in middleincome countries, and may be lower cost.…”
Section: Alternative Models Of Cr Delivery To Increase Reachmentioning
confidence: 99%